Winter Roost Preferences of Crows in Beijing City - Junyang Feng; Mengmeng Wang; Qianyi Zhang; Canwei Xia (Ecology and Evolution, 2025)
ABSTRACT During the winter season, an extensive population of crows (predominantly the carrion crow Corvus corone) seek refuge in Beijing's urban landscapes for roosting, subsequently generating noise and droppings that adversely affect the quality of life of residents. This study elucidates the selection criteria employed by crows in Beijing's urban areas for roosting sites. Drawing upon historical records and the outcomes of our survey, we observed a remarkable consistency in the selection of roosting locations by crows over time, with the same locations being preferentially chosen across different years. We also conducted a quantitative analysis of the habitat characteristics associated with the crow roosting sites. We discovered that crows demonstrate a preference for roosting sites situated in proximity to human structures, particularly towering buildings, which are often adjacent to broad roads. By understanding the factors that influence the selection of roosting sites by crows, policy‐makers and urban planners can devise targeted interventions aimed at mitigating conflicts between humans and crows.